Factors influencing adoption of renewable energy technology by high energy intensive firms in South Africa . - Magoro, Tshifhiwa Bernard. (My University, 2014)
ABSTRACT This report presents results of a research that investigated factors that influence adoption of renewable energy technology (RET) by energy intensive firms in South Africa. The analysis considered external environment factors, internal environment factors and technological attributes as three types of factors that are likely to be important. External environment factors are those external to the adopting organisation, which include public policy and stakeholders influence. Internal environment factors involve firm-level decision making, namely cost and benefit analysis, organisational capabilities and leadership values. Technology attributes are factors related to characteristics of the technology being adopted, which include compatibility, perceived benefits and relative advantage. The research design involved administering a questionnaire to all 36 members of the energy intensive user group of South Africa (EIUG), which is a professional association of industrial firms that accounts for a very high proportion of energy use in the country. The response rate was high (50%), with complete responses being received from representatives of 18 EIUG members. The key findings of this research are as follows: among EIUG members there is high level of awareness of RETs and firms viewed RET as credible technology to reduce their greenhouse gas (GHG) emissions. These firms are actively and continuously monitoring their own GHG emissions and majority have taken steps to adopt RETs but the momentum towards active and intensive adoption and deployment of RETs has simply not been reached. Internal environment factors and technological attributes are the two major concerns for firms wanting to adopt RET. The firms consider themselves to have strong leadership and organisational support for RET, but this is not reflected in sustained, wellresourced RET deployment strategies at firm-level. The most important finding of this research is that it starkly demonstrates the limited value of technology promotion and adoption strategies if they do not take firm-level decision making into account. The firms in this study reported that external environment factors such as public policy play only a limited role in influencing their adoption decisions. Importantly, these large industrial firms characterise the much vaunted renewable energy policy strategy (i.e. REFIT and Carbon Tax) as one that would only achieve minimum compliance.
MBA 2014
Keywords: Business enterprises -- Environmental aspects, Corporations,Renewable energy sources .